EFFECTS OF USING THE JAPANESE ABACUS METHOD UPON THE ADDITION AND MULTIPLICATION PERFORMANCE OF GRADE 3 INDONESIAN STUDENTS - Juliana Juliana; Lester C. Hao (Sanata Dharma University Yogyakarta, 2018)
This quasi-experimental study was conducted to determine the effect on accuracy and finish time of using the Japanese abacus method on the addition and multiplication performance of thirty Grade 3 pupils in selected schools in Indonesia. Fifteen formed the experimental group, were enrolled in abacus training classes outside of their respective schools, and were taught personally by the researcher through additional abacus treatment for ten meetings. The rest of the students formed the control group who do not use the abacus. Both groups were given the same pretest and posttest on addition and multiplication based on the Indonesian curriculum. Afterwards, students scores and finish time were analyzed using F-test and Students t-test. Results show that there is a significant difference between the experimental and control groups in terms of finish time in addition, scores in multiplication, and finish time in multiplication. Results also show that there is a significant increase in multiplication score in the experimental group from pretest to posttest. Student interviews, observations, and analyses of sample solutions revealed several errors that were parallel to Stiglers classification.DOI:https://doi.org/10.24071/ijiet.2018.020110